Use of a penicillin allergy clinical decision rule to enable direct oral penicillin provocation: an international multicentre randomised control trial in an adult population (PALACE): study protocol. Issue 8 (8th August 2022) - Copaescu, Ana-Maria; James, Fiona; Vogrin, Sara; Rose, Morgan; Chua, Kyra; Holmes, Natasha E; Turner, Nicholas A; Stone, Cosby; Phillips, Elizabeth; Trubiano, Jason
Abstract : Introduction: Penicillin allergies are highly prevalent in the healthcare setting and associated with the prescription of second-line inferior antibiotics. More than 85% of all penicillin allergy labels can be removed by skin testing and 96%–99% of low-risk penicillin allergy labels can be removed by direct oral challenge. An internally and externally validated clinical assessment tool for penicillin allergy, PEN-FAST, can identify a low-risk penicillin allergy without the need for skin testing; a score of less than 3 has a negative predictive value of 96.3% (95% CI, 94.1 to 97.8) for the presence of a penicillin allergy. It is hypothesised that PEN-FAST is a safe and effective tool for assessing penicillin allergy in an outpatient clinic setting. Methods and analysis: This is an international, multicentre randomised control trial using the PEN-FAST tool to risk-stratify penicillin allergy labels in adult outpatients. The study's primary objective is to evaluate the non-inferiority of using PEN-FAST score-guided management with direct oral challenge compared with standard care (defined as prick and intradermal skin testing followed by oral penicillin challenge). Participants will be randomised 1:1 to the intervention arm (direct oral penicillin challenge) or standard of care arm (skin testing followed by oral penicillin challenge, if skin testing is negative). The sample size of 380 randomised patients (190 per treatment arm) is required to demonstrate non-inferiority. Ethics and dissemination: The study will be performed according to the guidelines of the Helsinki Declaration and is approved by the Austin Health Human Research Ethics Committee (HREC/62425/Austin-2020) in Melbourne Australia, Vanderbilt University Institutional Review Board (IRB #202174) in Tennessee, USA, Duke University Institutional Review Board (IRB #Pro00108461) in North Carolina, USA and McGill University Health Centre Research Ethics Board in Canada (PALACE/2022-7605). The results of this study will be published and presented in various scientific forums. Trial registration number: NCT04454229 .